Collaborating with end-users in evidence synthesis: case studies for prevention in the first 2000 days - Alexandra Chung; Konsita Kuswara; Brittany J Johnson; Anna Lene Seidler; Alix Hall; Vicki Brown (Sax Institute, 2024)
Background: Evidence synthesis is an important tool to inform decision-making in public health policy and practice. Collaborative approaches to evidence synthesis involving researchers and the end-users of their research can enhance the relevance of the evidence for policy and practice and overcome the limitations of traditional evidence synthesis methods. Despite its benefits, collaboration is not consistently integrated into evidence-synthesis methods. Type of program or service: Collaborative evidence synthesis for public health policy and practice. Methods: Reflecting on our experiences of undertaking collaborative evidence syntheses with end-users to inform policy and practice around preventive health in the first 2000 days of life, we have collated our key learnings to inform future collaborations in public health research. Results: Key themes generated from our reflections were: 1) establish genuine partnerships early on with stakeholders, leveraging existing trusted relationships; 2) identify common goals; 3) prioritise evidence synthesis aims and objectives to ensure they are policy and practice relevant; and 4) maintain transparent, two-way communication. Lessons learnt: Collaboration involving researchers and end-users enhances knowledge synthesis methodologies, increases relevance and accessibility of the evidence for end-users, and strengthens research-policy relationships.